2005
DOI: 10.2991/jnmp.2005.12.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Jacobi, Ellipsoidal Coordinates and Superintegrable Systems

Abstract: We describe Jacobi's method for integrating the Hamilton-Jacobi equation and his discovery of elliptic coordinates, the generic separable coordinate systems for real and complex constant curvature spaces. This work was an essential precursor for the modern theory of second-order superintegrable systems to which we then turn. A Schrödinger operator with potential on a Riemannian space is second-order superintegrable if there are 2n − 1 (classically) functionally independent second-order symmetry operators. (The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In particular, reference [9] demonstrated that deformation of AdS 5 × S 5 to asymptotically-flat geometry by adding one to the harmonic function destroys integrability of sigma model, although the Hamilton-Jacobi equation for geodesics remains separable. The extension from AdS 5 × S 5 to flat geometry is only possible if one choses flat metric on the worldvolume of D3 branes 31 , and in section 3 we analyzed several classes of geometries produced by flat Dp branes. From the point of view of AdS/CFT correspondence, it is equally interesting to look at field theories on R × S 3 , which are dual to geometries produced by spherical D3 branes.…”
Section: Circles In Orthogonal Planesmentioning
confidence: 99%
“…In particular, reference [9] demonstrated that deformation of AdS 5 × S 5 to asymptotically-flat geometry by adding one to the harmonic function destroys integrability of sigma model, although the Hamilton-Jacobi equation for geodesics remains separable. The extension from AdS 5 × S 5 to flat geometry is only possible if one choses flat metric on the worldvolume of D3 branes 31 , and in section 3 we analyzed several classes of geometries produced by flat Dp branes. From the point of view of AdS/CFT correspondence, it is equally interesting to look at field theories on R × S 3 , which are dual to geometries produced by spherical D3 branes.…”
Section: Circles In Orthogonal Planesmentioning
confidence: 99%
“…then equation (B.42) ensures the symmetry of H. 45 Modifying the arguments that led to (B.22), we conclude that…”
Section: Jhep02(2014)061mentioning
confidence: 99%
“…As our final example of elliptic coordinates, we consider AdS 3 ×S 3 in global parameterization, which can be obtained by taking the near horizon limit (H → Q/f ) in (2.169) [63]: 37 We redefined angle θ in (2.199). Alternatively, one can keep (2.199) and shift θ in (2.74).…”
Section: 209)mentioning
confidence: 99%
“…37) There are p terms in this equation. Using the defining relation(3.15) for the CKYT, ∇ b Y acd... = −∇ a Y bcd... + 2g ab Z cd... − [g ca Z bd... + g cb Z ad... ] + .…”
mentioning
confidence: 99%